Photoinduced Processes in Silicon Nanoparticles - Martin, JÖRg; Cichos, Frank; Chan, Iu Y.; Huisken, Friedrich; Borczyskowski, Christian Von (Israel journal of chemistry, 2004)
Silicon nanocrystals have been prepared from gas‐phase pyrolysis and electrochemical etching of silicon. Confocal and wide‐field optical microscopy have been performed on size‐selected ensembles and single silicon nanocrystals. Single particles exhibit photoluminescence blinking effects that are interrelated with photo‐induced (reversible) bleaching effects of the ensemble. The blinking dynamics follow a power law statistic of on‐ and off‐times, revealing that even single nanoparticles are subject to strong disorder effects. This is supported by optically detected magnetic resonance (ODMR) experiments on silicon nanoparticles achieved for the first time via microscopic techniques.